Pendidikan Lingkungan dalam Novel dari Rahim Ombak Karya Tison Sahabuddin Bungin - Nanda Ananto; Juanda; Suarni Syam Saguni (ESTETIK : Jurnal Bahasa Indonesia, 2024)
This study aims to explore the aspects of environmental education in the novel Dari Rahim Ombak by Tison Sahabuddin Bungin. The method used in this study is qualitative with descriptive data description. The data source is the novel Dari Rahim Ombak. The data collection technique is a literature study by examining the content of environmental education values. In addition, the researcher read the novel to identify elements of the environmental education theme, and noted and quoted words, sentences, and paragraphs that describe the concept. The data analysis technique refers to an interactive analysis model that involves three main stages, namely data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that there are four aspects of environmental education, namely, an attitude of responsibility, an attitude of solidarity, an attitude of respect for nature, and environmental preservation. The findings show that the more dominant data is an attitude of solidarity towards nature. This proves that the novel Dari Rahim Ombak reveals that although Bungin Island has a majority of people as fish bombers, there are still some figures who care about the preservation of the sea and coral reefs. This study contributes as teaching materials in high schools and universities. This research can be used as teaching material by designing a module or teaching material based on the analysis of the novel Dari Rahim Ombak which links the theme of environmental education, then taught through discussions, text analysis assignments, and environmental awareness-based projects in high school and college classes. This research can also be the basis for government policy in suppressing the circulation of fish bombing actions.